Ritual Sedekah Bumi di Desa Teras Bendung Kecamatan Lebak Wangi Kabupaten Serang-Banten - Siti Fauziyah; Bustomi Bustomi (Tsaqofah, 2019)
Earth alms ritual in Teras Bendung Village, Lebak Wangi District, Serang Regency is held after harvest, in the form of earth alms ritual. According to the local community, the earth alms ritual ceremony is a form of expression of gratitude for the goddess Sri (the goddess of rice guards) and also to make a request to God Almighty for blessings and salvation. The focus of the problems in this research are: 1. what is the form of the earth alms tradition in Teras Bendung Village, 2. How is the function of the earth alms tradition in Teras Bendung Village, 3. What is the meaning of the earth alms tradition for the people of Teras Bendung. The objectives of this research are: 1. to reveal the form of the earth alms tradition in Teras Bendung Village, 2. to reveal the function of the earth alms ceremony in Teras Bendung Village, 3. to reveal the meaning in the earth alms ceremony in Teras Bendung Village, Lebak Wangi District, Serang Regency so that it can continue until now. This research method uses cultural research methods, namely surveys, participation, observation, interviews and documentation using anthropological and sociological approaches.